Analisis Tingkat Kepuasan Kerja Karyawan Pada PT Centradist Partsindo Utama Cabang Medan - Venny Venny; Wilinny Wilinny; Wong Pong Lan; Weny Weny; Fahmi Sulaiman (Forum Kerjasama Pendidikan Tinggi, 2021)
Job satisfaction is a very important thing to note so that all activities within the company can be run smoothly. Research on the level of job satisfaction at PT. Centradist Partsindo Utama Medan Branch started from the high level of employee absenteeism. Main Branch Medan. This study uses descriptive quantitative methods that aim to determine the level of job satisfaction of employees at PT. Centradist Partsindo Utama Medan Branch based on data obtained from questionnaires. The sampling technique used by the researcher is purposive sampling where the subjects in this study are all employees. who have worked for more than 2 years at PT. Centradist Partsindo Utama Medan Branch, as many as 21 people. research subjects where as many as 3 employees (14.3%) have a high level of job satisfaction, 15 employees (71.4%) have a moderate level of job satisfaction, and 3 employees (14.3%) have low job satisfaction